Intelligent Fixtures for the Manufacturing of Low Rigidity Components - Moehring, Hans Christian; Wiederkehr, Petra; Gonzalo, Oscar; Kolar, Petr.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The book summarizes the results of the European research project "Intelligent fixtures for the manufacturing of low rigidity components" (INTEFIX). The structure of the book follows the sub-projects which are dedicated to case studies within the scenarios "vibrations", "deformations" and "positioning". The INTEFIX project deals with the development and analysis of several exemplary types of intelligent, sensor and actuator integrated fixtures for the clamping of sensitive workpieces in cutting machine tools. Thus, the book gives a representative overview about this innovative field of technology. The demands of the case studies are described and the technological approaches and solutions are introduced. Furthermore, innovative methods for the design and optimization of intelligent fixtures are presented.
Part I Vibration -- Identiﬁcation and Active Damping of Critical Workpiece Vibrations in Milling of Thin Walled Workpieces -- Turning  of Low pressure Turbine casing --  Auto-adaptive Vibrations and Instabilities Suppression in General Milling Operations -- Part II Deformation -- Detection and Compensation of  Workpiece Distortions During Machining of Slender  and Thin-Walled Aerospace Parts -- Clamping of Thin-Walled Curved  Workpieces --  Distortions in Aeronautical Structural Parts -- Machining of Aircraft Turbine Support  Structures --  Part III Positioning.-  Fixture System for Workpiece Adjustment and Clamping with/Without Its Pre-deformation -- Semiautomatic Tool Reference for Application  on large Parts -- Active Fixtures for High Precision Positioning  of Large  parts for the Windmill Sector.
Keywords: Manufactures; Machinery; Mechanics, Applied; Machines, Tools, Processes; Machinery and Machine Elements; Engineering Mechanics